Identification and Expression Analysis of bZIP Members under Abiotic Stress in Mung Bean (Vigna radiata) - Wenhui Zhang; Shijia Ye; Yanli Du; Qiang Zhao; Jidao Du; Qi Zhang (Life, 2022)
The main aim of this study was to identify the bZIP family members in mung bean and explore their expression patterns under several abiotic stresses, with the overarching goal of elucidating their biological functions. Results identified 75 bZIP members in mung bean, which were unevenly distributed in the chromosomes (1–11), and all had a highly conserved bZIP domain. Phylogenetic analysis divided the members into 10 subgroups, with members in the same subgroup having similar structure and motif. The cis-acting elements in the promoter region revealed that most of the bZIP members might have the connection with abscisic acid, ethylene, and stress responsive elements. The transcriptome data demonstrated that bZIP members could respond to salt stress at different degrees in leaves, but the expression patterns could vary at different time points under stress. Differentially expressed genes (DEGs), such as VrbZIP12, VrbZIP37, and VrZIP45, were annotated into the plant hormone signal transduction pathway, which might be regulated the expression of abiotic stress-related gene (ABF). Quantitative real-time polymerase chain reaction (qRT-PCR) was applied to determine the expression of bZIP members in roots and leaves under drought, alkali, and low-temperature stress. Results showed that bZIP members respond differently to diverse stresses, and their expression was tissue-specific, which suggests that they may have different regulatory mechanism in different tissues. Overall, this study will provide a reference for further research on the functions of bZIP members in mung bean.